Kupas Isi Gurindam Dilihat dari Perspektif Islam - Suci Nurasyifa (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Gurindam Dua Belas is an ancient Malay poem by Raja Ali Haji. These twelve letters were written in the form of Gurindham poetry and contain many moral messages from educational, religious and cultural aspects. Apart from being a scholar, he is also known as the father of literature and a national hero of the Riau Islands province. He named it Gurindam twelve because there are twelve chapters consisting of two stanzas, each chapter consisting of two lines of the same poem, forming one complete unit. The first line contains questions, problems, or agreements, and the second line contains answers or results from the first line's questions or agreements. Gurindam twelve not only sounds beautiful when pronounced, but also conveys many moral messages, including appeals and advice in accordance with religious teachings and formal education. Gurindam twelve is specifically for all age groups, including children's obligations to their parents, parents' obligations to their children, the obligations of nobles towards society, karma, the advice of Almighty God, and living prosperously in society. Through his poem 'Gurindam Dua Belas', Raja Ali Haji aims to provide learning about consistent values, norms and ethics through teaching religion, education, politics, philosophy and law.